¿Nudo Gordiano? o ¿Laberinto sin salida? Visualizando una forma de atar cabos para asumir los desafíos de la administración actual (2019)
Diverse social dysfunctions within contemporary societies are the consequences of prevailing short-sighted administrative ideas and practices. The first part of this article examines such problematic relations and states the need to renew mental representations and pedagogic strategies that influence the field of administration. The central body of the articles evokes the mythical figures of Midas and These in order to approach some pathological traits of mainstream management and common economic reasoning. These myths are recalled as well to inspire alternative conceptions and deeds to renew management, so it can better face the challenges confronting human communities.